SIGNIFICANCE OF THE ALGORITHMS ON MINIMIZATION OF RIGHT-VENTRICULAR ELECTROSTIMULATION IN PREVENTION OF ATRIAL FIBRILLATION PROGRESSION IN PATIENTS WITH SICK SINUS SYNDROME - A. E. Ivanchina; F. Yu. Kopylov; I. V. Samoilenko; A. L. Syrkin; M. V. Serova (Кардиоваскулярная терапия и профилактика, 2017)
Aim. To assess the efficacy of algorithms for minimization of the rightventricular stimulation (MVS) for prevention of atrial fibrillation (AF) progression in patients with sick sinus node syndrome (SSS) and documented AF in anamnesis, comparing to standard bi-chamber electrical stimulation (DDDR).Material and methods. The study was one-center, prospective, randomized trial with consequent 74 patients inclusion, who had indications to permanent DDDR due to SSS and AF in anamnesis. Patients were randomized to DDDR group (n=36) and active MVS (n=38) group. Procedure of electrocardiostimulator (ECS) maintenance was done at 6 months and 1 year. During follow-up visits, information was saved in the ECS memory, as the data on AF burden. Primary endpoints were AF burden and time to persistent AF onset.Results. During the study, there were no significant differences in AF burden between the groups. Median of AF burden was 6,0 min/day (25- 75 percentiles: 0-42 min/day) in DDDR, and 6,0 min/day (25-75 perc.: 0-42 min/day; p=0,67) in MVS group. Persistent AF development was registered in 5 patients, of those 3 (8,6%) in DDDR and in 2 (5,3%) in MVS (HR 1,25; 95% CI 0,2-7,98; p=0,47). Medication or electrocardioversion was done for 9 (25,7%) patients from DDDR and 12 (31,6%) from MVS groups (HR 0,86, 95% CI 0,31-2,38, p=0,39).Conclusion. There was no benefit of MVS algorithms in short term period in decrease of AF burden and in its progression prevention towards persistent AF in SSS patients with the anamnesis of paroxysmal AF, comparing to standard DDDR regimen of ECS.